CFD investigation on combustion and NOx emission characteristics in a 600 MW wall-fired boiler under high temperature and strong reducing atmosphere. (5th November 2017) - Du, Yongbo; Wang, Chang'an; Lv, Qiang; Li, Debo; Liu, Hu; Che, Defu
Highlights: High temperature and strong reducing combustion was realized in unity boiler. Deep air stage and mixing O2 to secondary were used in combination. NO x was reduced by about 60% via the proposed method. Simulation results agrees well to the industrial test. Abstract: In this paper, a modified air staging technology for pulverized coal boilers was proposed, to notably reduce NO x emission by creating a zone with high temperature and strong reducing atmosphere (HT&SRA) in furnace. Here, the conventional air staging technology was employed in combination with increasing O2 fraction of feeding gas in primary zone ( O2 .p ). The new technology was numerically verified in a 600 MW wall-fired boiler and the temperature distribution, the char burnout and the effectiveness in NO x reduction were mainly examined. The results indicate that a sufficiently low stoichiometric O2 ratio in primary zone ( SR p ) is essential to reduce NO x emission by increasing O2 .p . The effectiveness in NO x reduction by increasing O2 .p also depends greatly on the injection position of over fire air (OFA). Under the condition of 0.7 SR p and a relatively high OFA position, the NO x emission could be reduced by 27.6% when O2 .p is increased from 21% to 33%, while the incomplete combustion heat loss only shows a slight rise. In addition, the NO x reduction ratio could reach to >60% through the proposed low-NO x combustion technology compared with the current operation condition.